Pengaruh Literasi Keuangan, Sikap dan Kepribadian Terhadap Perilaku Keuangan UMKM - Fachrurazi; Sutama Wisnu Dyatmika; Endi Rustendi; Made Susilawati; Musran Munizu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Micro, Small and Medium Enterprises (MSMEs) are an important part of the country and regions in increasing economic growth and reducing poverty. For countries with low per capita income, MSMEs are one of the indicators of successful development. Therefore, the government continues to strive so that MSMEs can continue to grow and develop. This study aims to determine the effect of financial literacy, financial attitudes, and personality on the financial behavior of MSMEs. This study is included in causal associative research. The respondents of this study were 96 wholesale and retail MSMEs. The primary data collection technique used a questionnaire instrument. Validity and reliability tests were carried out on the research data. The prerequisite analysis tests carried out included linearity tests, multicollinearity tests, and heteroscedasticity tests. The data analysis method in this study used multiple linear regression. The results of this study indicate that financial literacy, financial attitudes, and personality have a positive and significant effect on the financial behavior of MSMEs.